The Microbiome-Gut-Brain Axis and Resilience to Developing Anxiety or Depression under Stress - Tracey Bear; Julie E. Dalziel; Jane Coad; Nicole C. Roy; Christine A. Butts; Pramod K. Gopal (2021)
Episodes of depression and anxiety commonly follow the experience of stress, however not everyone who experiences stress develops a mood disorder. Individuals who are able to experience stress without a negative emotional effect are considered stress resilient. Stress-resilience (and its counterpart stress-susceptibility) are influenced by several psychological and biological factors, including the microbiome-gut-brain axis. Emerging research shows that the gut microbiota can influence mood, and that stress is an important variable in this relationship. Stress alters the gut microbiota and plausibly this could contribute to stress-related changes in mood. Most of the reported research has been conducted using animal models and demonstrates a relationship between gut microbiome and mood. The translational evidence from human clinical studies however is rather limited. In this review we examine the microbiome-gut-brain axis research in relation to stress resilience.